Analisis Penilaian Kinerja Menggunakan Balance Score Card - Armansyah Alipok; Nilawaty Yusuf; Siti Pratiwi Husain (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2021)
The research objective was to analyze the performance of drinking water depot in Gorontalo City by using a Balanced scorecard. The data were collected by using a quesionnaire. The data analysis applied descriptive analysis, which referred to the balanced scorecard indikator. The samples were 21 drinking water depots in Gorontalo city. The finding of research showed that the score in the balanced scorecard for the performance of drinking water depot in Gorontalo city was 81,39% which was in “minimum target” criteria, which meant the performance remained not in accordance with the expectation whether in the aspect of finansial or non finansial. The low finansial performance was the factor for the closing of lots of drinking water depot in Gorontalo city due to encountering problems in finansial and operational.